Prevalence of factors associated with cancer in medical students and sex-related diferences - Januário de Oliveira, Gabriela; de Assunção Santiago Fernandes, Amanda; Kelly de Souza Silva, Sara; Maldonado, Michelli; Torreglosa Ruiz Cintra, Mariangela; Wide Pissetti, Cristina (Seven Editora, 2023)
Introduction: Currently, there is an increase in the prevalence of chronic diseases, such as cancer. At the university, the acquisition of risky habits for this may be worrisome in the future. Thus, the assessment of the susceptibility of medical students can help to elucidate possible points of intervention, since it is a portion of the population oriented and supposedly encouraged to develop a healthy lifestyle. Objective: To evaluate the presence of risk factors associated with cancer in medical students at a public university in Paraíba. Patients and Methods: Cross-sectional and quantitative study was conducted with students from the first to the fourth year of the medical course at a public university. An objective questionnaire was used on the habits of sun and sexual exposure, dietary patterns, physical exercise, alcoholism, smoking, and others. The Chi-square test was used to assess the association between variables. The confidence interval and the level of significance considered were 95% and 5%, respectively. Results: A total of 211 students participated in the study. Of these, 35.5% reported using sunscreen. There was an association between the use of sunscreen and the female gender (p